Model of multi-stakeholder forest management: a system study of Protected Forest Management Unit in Solok, Indonesia - Ilham, Q.P.; Purnomo, H.; Nugroho, T. (IOP Publishing, 2019)
Multi-stakeholders forest management can be influenced by many factors and will be difficult because of different process expectations. This paper discusses the integration of soft systems methodology (SSM) within a multi-stakeholder approach in research to support sustainable and equitable forest management of the Protected Forest Management Unit (PFMU) in Solok, Indonesia. The management of PFMU in Solok is complicated by the legitimacy of forest right, institutional culture, political interest, uncertainty the nature of relationships among stakeholders, illegal logging, and the topography is varied, existing watersheds and limitations of forest inventory data. The situation is not only characterized by its complex ecosystem but, more importantly, by the complexity of the social and political system around it. In this work, SSM contributed to expressing the problem situations of PFMU. A model was developed by formulating the root definitions and building the conceptual model of the relevant component of forest management. The model was used to stimulate debate about desirable and feasible change, as well as to explore the future scenarios. Finally, multi-stakeholders approach by implementing the SSM principle helps to harmonize the stakeholder interest and to formulate the scenario of forest management. This approach was also found to be a positive way to explore a collaborative action plans for sustainable and equitable forest management.